2010
DOI: 10.1016/j.cej.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the reactivity of metallic iron in Fe0/EDTA/H2O systems with column experiments

Abstract: Characterizing the intrinsic reactivity of iron materials for environmental remediation has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…As was leached from a natural rock using the tap water of the city of Göttingen as leaching solution. The results confirmed findings from previous works that ZVI2 is the least reactive material (Noubactep et al, 2005;Noubactep, 2010a, Noubactep 2011d. It could further be shown that ZVI1 is less reactive than ZVI3 and ZVI4.…”
Section: Discussionsupporting
confidence: 81%
“…As was leached from a natural rock using the tap water of the city of Göttingen as leaching solution. The results confirmed findings from previous works that ZVI2 is the least reactive material (Noubactep et al, 2005;Noubactep, 2010a, Noubactep 2011d. It could further be shown that ZVI1 is less reactive than ZVI3 and ZVI4.…”
Section: Discussionsupporting
confidence: 81%
“…The present section characterizes the efficiency of tested materials in term of (i) iron release, (ii) MB discoloration and (iii) permeability loss. [32,33,35]. The observed differential behaviour can be attributed to the presence of fines as ZVI9 and ZVI10 content more fines than ZVI1.…”
Section: Mb Column Testmentioning
confidence: 87%
“…3 and vary from 13 μg h -1 for ZVI8 to 37 μg h -1 for ZVI10. The least reactive material (ZVI8 from Würth) was used as negative reference like in previous studies [32][33][34]. The most reactive material were ZVI9 (Ferblast) and ZVI10 (Peerless).…”
Section: Edta Batch Test 421 All Tested Materialsmentioning
confidence: 99%
“…Accordingly, results of experiments performed following the concept presented herein will enable the determination of´q 0 and, thus, v p . Then v 0 can be obtained from short-term column experiments using, for example, diluted EDTA solutions [176]. These parameters will enable a better design of Fe 0 filters.…”
Section: Filter Design Considerationsmentioning
confidence: 99%
“…Because steel wool is simply the starting material for a hand-built and locally sourced water filter, there is a real potential to foster local industry during filter construction, which includes: (i) designing and manufacturing plastic or glass filter containers; (ii) purchasing and conditioning Fe 0 materials (including steel wool) and additives; and (iii) collecting and recycling spent (corroded) filters [122,127,169,176]. Testing metal foams should be also considered in this effort [177].…”
Section: Steel Wool Filters For Allmentioning
confidence: 99%